Penegakan Hukum Tindak Pidana Narkotika : Studi Kasus Nomor 1248/Pid.Sus/2023/PN Mdn - Marbun, Hissah Kristina; Lala Anggina Salsabila; Tatiadinata Saragih; Parlaungan G. Siahaan; Dewi Pika Lbn Batu (Lembaga Pengembangan Kinerja Dosen, 2023)
This article aims to examine what law enforcement is like in class 1 narcotics crime cases and based on Law of the Republic of Indonesia Number 35 of 2009 concerning narcotics which has been proven. This research uses the method. This research was carried out by examining the main problem through a juridicalnormative approach so that in terms of its type, this research is normative legal research. The scope of normative legal research in this research is limited to legal history in the form of court decisions that have permanent legal force against narcotics abusers in the jurisdiction of the Medan District Court.